The Externalization of European Borders: The Other Face of Coloniality Turkey as a Case Study - Afailal, Hafsa (2018)
Turkey’s border controls were not a priority as they have been for the Schengen Europe, but the negotiations to access the European Union and the recent agreement on tighter migration controls transformed this open behaviour into a more conservative one, through the externalization process of the European borders. This article focuses on how the new organisational models of power relations can be explained through the theory of the coloniality of power, marked by a Eurocentric form of imposition. The construction of the externalised European borders represents a new form of coloniality, classifying the population (migrant vs. EU citizen) and the countries (EU members vs. countries where control has been externalised to) according to the level of threat they represent for the EU. As a result of these dynamics, Turkey has a new migration policy that is quite selective deciding who might or might not enter the fortress, replicating this way the difficulties of navigating the European migration policy, despite the fact that the country is not a member of the European Union.